2013
DOI: 10.1038/ncomms3306
|View full text |Cite
|
Sign up to set email alerts
|

Doping of polycrystalline CdTe for high-efficiency solar cells on flexible metal foil

Abstract: Roll-to-roll manufacturing of CdTe solar cells on flexible metal foil substrates is one of the most attractive options for low-cost photovoltaic module production. However, various efforts to grow CdTe solar cells on metal foil have resulted in low efficiencies. This is caused by the fact that the conventional device structure must be inverted, which imposes severe restrictions on device processing and consequently limits the electronic quality of the CdTe layer. Here we introduce an innovative concept for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(164 citation statements)
references
References 32 publications
4
160
0
Order By: Relevance
“…The resistivity of the pure CdTe with different amounts of Cu added is comparable with previously published results [30]. A substantial increase in resistivity is observed if less than approximately 1 × 10 15 copper atoms/cm 2 are added.…”
Section: Resultssupporting
confidence: 89%
“…The resistivity of the pure CdTe with different amounts of Cu added is comparable with previously published results [30]. A substantial increase in resistivity is observed if less than approximately 1 × 10 15 copper atoms/cm 2 are added.…”
Section: Resultssupporting
confidence: 89%
“…[10][11][12][13] In this method, the electron beam of a scanning electron microscope (SEM) is used to generate excited charge carriers that are, in turn, collected as a measurable current for producing two-dimensional maps of the SCE. Although this method has yielded important insights into charge transport mechanisms in thin-film PV cells, the need for cross-section lamellas and operation in vacuum conditions make it destructive and render it difficult to evaluate devices under real operating conditions.…”
Section: Context and Scalementioning
confidence: 99%
“…18,19 In addition, electron beam induced current (EBIC), as described in ref. [20][21][22][23], requires fabrication of full device stacks that are measured under vacuum, which prohibits use of this method for characterization of photoelectrochemical systems under real operating conditions. To overcome this characterization gap and extract the diffusion length, Pala et al 24 suggested measuring photocurrent changes in wedge-shaped thin films.…”
Section: Introductionmentioning
confidence: 99%